A Fuzzy Rule based Expert System for T2DM Diagnosis - D.Dhivya, A.; Felix, A. (International Journal of Engineering and Technology, 2018)
Expert system is an intelligent system to captures the knowledge of a human expert in a specific area. It is capable to make decisions and dealing with ambiguous data. It is used to take an expert view in the absence of a human expertise. Moreover, it is not possible that everyone is expert in every field; to overcome this kind of situation, the expert system is called to handle the complex cases [7]. Due to non availability of the doctor, sometimes patient's life is in risk and lead to death due to not diagnose the disease properly as there are several diseases whose symptoms are quite similar in initial stage. Hence, the objective of this paper is to design the expert system for diagnosing the diabetes to go for early treatment.Â Â